ANALISIS PERKUATAN STRUKTUR BETON MENGGUNAKAN METODE CONCREATE JACKETING DAN FIBER REINFORCED POLYMER (FRP) - Sarah Azzima Suherman; Budi Kudwadi; Ben Novarro Batubara (Matriks Teknik Sipil, 2025)
Structural damage is usually found in buildings that have changed function and are old. Damage can affect the feasibility of the building. Repair and strengthening of building structures need to be done so that the development goals can be achieved again. The purpose of this study was to determine the structural strength of the existing Rusunawa Cingised building in Bandung City and its reinforcement using the concrete jacketing method and the FRP method. The research method uses comparative research to explore the differences between two or more situations, events, activities, or plans. The data collection technique uses purposive sampling. The analysis method is carried out using SAP2000 software by entering dead loads, live loads, wind loads according to SNI, and earthquake response spectrum loads. Columns that do not meet capacity are further analyzed and their reinforcement is planned using two methods, namely concrete jacketing and FRP. From the analysis results, the existing columns from the ground floor to the 4th floor columns with the same dimensions of 350x350 mm, there are 17 columns that do not meet the structural capacity. Reinforcement was carried out using the concrete jacketing method, the number of columns reinforced with jacketing became dimensions of 550x550 mm as many as 23 pieces spread across the ground floor, 1st floor, and 2nd floor. Meanwhile, in FRP reinforcement, it requires 5 layers of 1.2 thick carbon fiber, installed on the columns from the ground floor to the 1st floor.Keywords: building; concrete jacketing; existing building; Fiber Reinforced Polymer (FRP); reinforcement; SAP2000